Negative situation appraisal and mental well-being among refugees in Germany: Serial mediation by religious coping and sense of coherence - Sebastian Binyamin Skalski-Bednarz; Karol Konaszewski; Jolanta Muszyńska; Kathrin Maier; Janusz Surzykiewicz (International Migration, 2022)
It has been widely demonstrated that pre- and post-migration experiences can be highly traumatic for refugees. The purpose of this study was to assess the mediating effects of religious coping and sense of coherence on the association of negative dysfunctional situation appraisal and mental well-being among refugees. Paper surveys were completed by 600 people representing various refugee groups (mostly from Mashreq Countries) in German Bavaria, aged 18–65. Mediation analysis revealed that negative religious coping and sense of coherence singly and serially mediated the relationship between negative dysfunctional situation appraisal and well-being, whereas positive religious coping did not have statistically significant relationships with these variables. The data obtained suggest that the negative religious coping style and sense of coherence are two important targets for future experimental studies, and interventions on them may bring the synergistic effect on improving mental well-being in refugees.
Keywords: 300